Scratch-Assisted Computational Thinking in Physics: A Literature Review - Herawati, Nadya Intan; Kuswanto, Heru; Wahyuni, Mustika; Aristaria, Anggriani (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
One of the competencies needed in 21st century learning is Computational Thinking. Computational Thinking is a type of analytical thinking that uses mathematical thinking as an approach to solving a problem, designing a system, and evaluating a large and complex system so that it can be operated in the real world. In the context of the link between physics learning and computational thinking, media is needed in the learning process. One learning media that can help students learn abstract concepts is Scratch.The purpose of this research is to analyze the use of scratch in Computational Thinking skills in physics learning. The method used in this research is a literature review. The literature review was carried out by searching for keywords, namely: scratch, computational thinking, and physics. Collection of literature sources obtained from various sources through national and international journals. We obtained 25 articles that matched the keywords. These articles have been filtered by year of publication, over the last ten years. In addition to the effectiveness of scratching we investigate the impact of scratching. The results showed that after playing scratch the students' Computational Thinking abilities increased significantly.